Studying Tree Responses to Extreme Events - Cristina Nabais (Frontiers Research Topics, 2017)
Trees are among the longest-living organisms. They are sensitive to extreme climatic events and document the effects of environmental changes in form of structural modifications of their tissues. These modifications represent an integrated signal of complex biological responses enforced by the environment. For example, temporal change in stem increment integrates multiple information of tree performance, and wood anatomical traits may be altered by climatic extremes or environmental stress. Recent developments in preparative tools and computational image analysis enable to quantify changes in wood anatomical features, like vessel density or vessel size. Thus, impacts on their functioning can be related to climatic forcing factors. Similarly, new developments in monitoring (cambial) phenology and mechanistic modelling are enlightening the interrelationships between environmental factors, wood formation and tree performance and mortality. Quantitative wood anatomy is a reliable indicator of drought occurrence during the growing season, and therefore has been studied intensively in recent years. The variability in wood anatomy not only alters the biological and hydraulic functioning of a tree, but may also influence the technological properties of wood, with substantial impacts in forestry. On a larger scale, alterations of sapwood and phloem area and their ratios to other functional traits provide measures to detect changes in a tree's life functions, and increasing risk of drought-induced mortality with possible impacts on hydrological processes and species composition of plant communities. Genetic variability within and across populations is assumed to be crucial for species survival in an unpredictable future world. The magnitude of genetic variation and heritability of adaptive traits might define the ability to adapt to climate change. Is there a relation between genetic variability and resilience to climate change? Is it possible to link genetic expression and climate change to obtain deeper knowledge of functional genetics? To derive precise estimates of genetic determinism it is important to define adaptive traits in wood properties and on a whole-tree scale. Understanding the mechanisms ruling these processes is fundamental to assess the impact of extreme climate events on forest ecosystems, and to provide realistic scenarios of tree responses to changing climates. Wood is also a major carbon sink with a long-term residence, impacting the global carbon cycle. How well do we understand the link between wood growth dynamics, wood carbon allocation and the global carbon cycle? Papers contribution to this Research Topic will cover a wide range of ecosystems. However, special relevance will be given to Mediterranean-type areas. These involve coastal regions of four continents, making Mediterranean-type ecosystems extremely interesting for investigating the potential impacts of global change on growth and for studying responses of woody plants under extreme environmental conditions. For example, the ongoing trend towards warmer temperatures and reduced precipitation can increase the susceptibility to fire and pests. The EU-funded COST Action STREeSS (Studying Tree Responses to extreme Events: a SynthesiS) addresses such crucial tree biological and forest ecological issues by providing a collection of important methodological and scientific insights, about the current state of knowledge, and by opinions for future research needs.